2022
DOI: 10.2174/1871527320666210212112651
|View full text |Cite
|
Sign up to set email alerts
|

Dioclea Altissima Seed Lectin (DAL) Prevents Anxiety-like Behavioral Responses in Adult Zebrafish (Danio Rerio): Involvement of GABAergic and 5-HT Systems

Abstract: Background: Plant lectins has shown promising neuropharmacological activities in animal models. Objective: This study evaluated the effect of Dioclea altissima seed lectin (DAL) on adult zebrafish behavior. Method: Zebrafish (n=6/group) were treated (i.p.; 20 µL) with DAL (0.025; 0.05 or 0.1 mg/mL), vehicle or diazepam (DZP) and submitted to several tests (open field, light/dark preference or novel tank). Flumazenil, pizotifen or granisetron were administered 15 min before DAL (0.05 mg/mL), and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…The monoaminergic system [serotonin (5-HT) and dopamine (DA)] in the brain has been postulated to play an important role in the pathophysiology of anxiety disorders [26][27][28]. Several preclinical and clinical reports provide evidence to support that a dysfunction of the monoaminergic system may be implicated in the pathophysiology of anxiety disorders [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The monoaminergic system [serotonin (5-HT) and dopamine (DA)] in the brain has been postulated to play an important role in the pathophysiology of anxiety disorders [26][27][28]. Several preclinical and clinical reports provide evidence to support that a dysfunction of the monoaminergic system may be implicated in the pathophysiology of anxiety disorders [26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…The monoaminergic system [serotonin (5-HT) and dopamine (DA)] in the brain has been postulated to play an important role in the pathophysiology of anxiety disorders [26][27][28]. Several preclinical and clinical reports provide evidence to support that a dysfunction of the monoaminergic system may be implicated in the pathophysiology of anxiety disorders [26][27][28][29][30]. Zhang et al [26] have shown that the modulation of the monoaminergic system forms the basis for the action of anxiolytic drugs, and this hypothesis provides a framework in which the pathophysiology and pharmacotherapy for anxiety may congregate on the modulation of monoaminergic system.…”
Section: Introductionmentioning
confidence: 99%